Performance and Effectiveness Evaluation of the National Digital Samsat as a Public E-Government Service Using the PIECES Framework - Fitria, Rahma; Syakhila, Amanda; Yulisda, Desvina; Hussain, Azham; Febriandirza, Arafat (Innovation in Research of Informatics (Innovatics), 2025)
The SIGNAL application is a digital service from the Korlantas Polri that makes it easier for people to take care of STNK validation online. However, some users still experience problems such as the verification process that is not always successful, slow delivery of physical documents, less rapid customer service response, and slow verification or login process. Therefore, this study aims to evaluate the performance of the SIGNAL application with the PIECES framework approach which includes six aspects: Performance, Information, Economic, Control, Efficiency, and Service. The data collection method was carried out through distributing questionnaires to 300 respondents who use the SIGNAL application. In addition, technical performance testing was also carried out using Apptim tools to measure application technical metrics. The results showed that overall, users were satisfied with the system based on the six aspects of PIECES with an average score of 3.9 on a scale of 5.76% of respondents stated that they were satisfied to very satisfied, 15% were undecided/neutral, and 9% were dissatisfied. This finding indicates that the majority of users consider this application to be quite effective and worth using. Performance testing using Apptim resulted in an average response time of 2.4 seconds, CPU usage of 18%, memory usage of 170MB, and no errors (error rate 0%), indicating that the application is quite stable and runs well on user devices. It is hoped that this research can be the basis for further development of the SIGNAL application, especially in improving service aspects and overall system efficiency.